Comprehensive Profiling of the Rheumatoid Arthritis Antibody Repertoire. Issue 2 (29th December 2019) - Lo, Ken C.; Sullivan, Eric; Bannen, Ryan M.; Jin, Huiyan; Rowe, Mark; Li, Hanying; Pinapati, Richard S.; Cartwright, Adam J.; Tan, John C.; Patel, Jigar; Keystone, Edward C.; Siminovitch, Katherine A.
Abstract : Objective: Autoantibodies against citrullinated proteins are found in 64–89% of rheumatoid arthritis (RA) patients, with 88–99% specificity. This study was undertaken to create an unbiased, comprehensive profile of serum antibodies against the human proteome, including the citrullinome and the homocitrullinome, in RA patients, using a high‐density peptide array. Methods: Our high‐density peptide array, consisting of >4.6 million peptides, contained the entire annotated human proteome. The 20, 246 proteins were represented as overlapping 16‐mer peptides. In addition to native peptides, citrullinated and homocitrullinated peptides were included, as substitutions for arginine and lysine, and provided a comprehensive screen against all possible epitopes. Twenty‐six serum samples (from 8 controls and 18 RA patients) were profiled on the high‐density peptide array. Using RA‐specific epitopes, we constructed an 8‐epitope diagnostic biomarker on a Gyrolab xPlore instrument with a cohort of 92 serum samples (from 29 controls and 63 RA patients). The diagnostic biomarker was further validated with an independent cohort of 181 serum samples (from 54 controls and 127 RA patients). Results: In the initial cohort the diagnostic performance of the 8‐epitope biomarker yielded 96.6% specificity and 92.1% sensitivity. The overall diagnostic performance in the validation cohort was 94.4% specificity and 85% sensitivity. In both cohorts, the performance of the 8‐epitope diagnostic biomarker compared favorably against the Abnova cyclic citrullinated peptide 2 (CCP2) assay. Using data from the peptide array, we identified novel RA‐specific epitopes and formed the basis of a new RA diagnostic assay. Conclusion: Comprehensive antibody profiling using a high‐density peptide array not only identified novel RA‐specific epitopes but also allowed us to construct a novel diagnostic biomarker that is as specific as and more sensitive than the Abnova CCP2 assay.